Group Pay-For-Performance Plans: The Role of Spontaneous Goal Setting - Hollensbe, Elaine C.; Guthrie, James P. (Academy of Management Review, 2000)
Despite the increasing popularity of group pay-for-performance plans, relatively little theory exists regarding the dynamics of these plans. We integrate goal setting, pay plan characteristics, and group factors to explain and predict the effectiveness of what we call “open-goal” group pay plans. We introduce spontaneous goal setting as a process explanation and propose antecedents that affect a group's propensity to set goals, the goal level chosen, and goal commitment. Finally, we discuss implications of our propositions for future research.